The Effect of Exogenous Bile Acids on Antioxidant Status and Gut Microbiota in Heat-Stressed Broiler Chickens - Yin, Chang; Xia, Bing; Tang, Shanlong; Cao, Aizhi; Liu, Lei; Zhong, Ruqing; Chen, Liang; Zhang, Hongfu (Frontiers in Nutrition, 2021)
Bile acids (BA) are critical for lipid absorption, however, their new roles in maintaining or regulating systemic metabolism are irreplaceable. The negative impacts of heat stress (HS) on growth performance, lipid metabolism, and antioxidant status have been reported, it remains unknown whether BA composition of broiler chickens can be affected by HS. This study therefore aimed to investigate the modulating effects of the environment (HS) and whether dietary BA supplementation can benefit to heat-stressed broiler chickens. A total of 216 Arbor Acres broilers were selected with body weight approach average and treated with thermal neutral (TN), HS (32℃) or HS-BA (200 mg/kg BA supplementation) from 21d to 42d. The results showed that birds in HS-BA group had the higher average daily gain and feed conversion ratio compared with HS group (P<0.05), while the GSH-Px activities in both serum and liver were restored to the normal range were observed (P<0.05). HS caused a drop in the primary BA (P=0.084, 38.46%) and tauro-conjugated BA (33.49%) in ileum, meanwhile, the secondary BA in the liver and cecum were lower by 36.88% and 39.45% respectively. Notably, results were consistent that SBA levels were significantly increased in the serum (3-folds, P=0.0003) and the ileum (24.89 folds, P<0.0001). Among them, TUDCA levels (P<0.01) were included. Besides, BA supplementation indeed increased significantly TUDCA (P=0.0154) and THDCA (P=0.0003) in the liver while TDCA (P=0.0307), TLCA (P=0.0453), HDCA (P=0.0018), and THDCA (P=0.0002) levels under the HS. Intestinal morphology of ileum was observed by hematoxylin and eosin (H＆E) staining, birds fed with BA supplementation reduced (P=0.0431) crypt depth, and the ratio of villous height to crypt depth trended higher (P=0.0539) under heat exposure. Quantitative RT-PCR showed that dietary supplementation with BA resulted in upregulation of FXR (P=0.0369), ASBT (P=0.0154), and Keap-1 (P=0.0104) while downregulation of iNOS (P=0.0399) expression in ileum. Moreover, 16S rRNA gene sequencing analysis and relevance networks revealed that HS-derived changes in gut microbiota and BA metabolites of broilers may affect their resistance to HS. Thus, BA supplementation can benefit broiler chickens during high ambient temperatures, serving as a new nutritional strategy against heat stress.